TINDAK KEKERASAN TERHADAP JAMAAH AHMADIYAH INDONESIA: SEBUAH KAJIAN PSIKOLOGI SOSIAL - Hakim, Lukman Nul (Jurnal Aspirasi, 2011)
This article studies the violence towards Jamaah Ahmadiyah member from social psychology perspective. It tries to find out the process of how the negative attitudes formed and how we can resolve them. Some factors contribute to the formation of negative attitude towards Jamaah Ahmadiyah members, such as benchmark policy from another country towards Jamaah Ahmadiyah, government decision, fatwa from an Islamic Cleric Groups, statement from prominent people, weak law enforcement, and so forth. A comprehensive action should be implemented to overcome the problem.